2015
DOI: 10.4172/2329-888x.1000123
|View full text |Cite
|
Sign up to set email alerts
|

Active Dry Yeast Culture Supplementation Effect on the Blood Biochemical Indicators of Dairy Goats

Abstract: The aim of study was to assess the feeding level on a commercial farm and to evaluate the effect of active dry yeast culture supplementation on blood indicators of dairy goats. Eighteen goats were divided into control and experimental groups. Beginning one week before expected kidding does in experimental group were supplemented 10 g/day/goat of yeast until 100d post-partum, after which the dose was increased to 20 g/day/goat. Blood samples were taken on days 7, 30, 80, 120 and 180 of lactation. There were dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 14 publications
2
1
0
Order By: Relevance
“…However, the difference was observed at the beginning and at the end of the experiment, therefore, it is not possible to independently confirm that the yeast supplement affected the Ca and Mg absorption. BAGnICKA et al (2014) found that YS improved the intestinal absorption of calcium in goats, similar to our study. Nevertheless, the mechanisms underlying the increased absorption of Ca are not fully elucidated (GIlMAn and CASHMAn, 2006).…”
Section: Resultssupporting
confidence: 91%
“…However, the difference was observed at the beginning and at the end of the experiment, therefore, it is not possible to independently confirm that the yeast supplement affected the Ca and Mg absorption. BAGnICKA et al (2014) found that YS improved the intestinal absorption of calcium in goats, similar to our study. Nevertheless, the mechanisms underlying the increased absorption of Ca are not fully elucidated (GIlMAn and CASHMAn, 2006).…”
Section: Resultssupporting
confidence: 91%
“…Further, Fe, Cu, Zn levels were approximately 3, 0.3, 2 times more from Fathy Nawito et al (2015)'s results, respectively. But then, an overlapping results was obtained in terms of 3 minerals reported by Bagnicka et al (2014). The value of Mn in the Pitropovska et al (2014)'s report was higher than that of the 2 years-old young animals in this study.…”
Section: Discussionsupporting
confidence: 59%
“…Moreover, in a study carried out by Yatoo et al (2013), Fe, Cu, Zn and Mg were determined as 1.548±0.173 mg/L, 0.548±0.094 mg/L, 0.864±0.211 mg/L and 2.11±0.24 mmol/L, respectively. In another study carried out by Bagnicka et al (2014), Fe, K and Mg were presented as 21.54 µmol/l, 3.59 mmol/L, 0.79 mmol/L at the end of lactation period (180 th day), respectively. Furthermore, Fathy Nawito et al (2015) demonstrated Fe, Cu and Zn levels as 4.91±0.09 ppm, 0.49±0.05 ppm, 4.65±0.24 ppm in non-pregnant goats reared in South Sinai, Egypt, respectively.…”
Section: Discussionmentioning
confidence: 95%